Characterization of immunologically detectable T-cell sensitization, Immunohistochemical detection of pro-inflammatory cytokines, and clinical parameters of patients after allogeneic intraoral bone grafting procedures: a prospective randomized controlled clinical trial in humans - Önder Solakoglu; Werner Götz; Volker von Baehr; Guido Heydecke; Klaus Pantel; Heidi Schwarzenbach (BMC, 2022)
Abstract Background The null hypotheses were tested that intraoral bone augmentation using two different allogeneic materials has no impact on the patient's blood levels of material-specific lymphocytes and on the immunohistochemical detection of pro-inflammatory cytokines IL-1α, IL1ß and TNF-α and T-cell markers CD4, CD8 in biopsies of the test groups. Methods In this prospective RCT, 60 systemically healthy participants were randomly assigned to two allogeneic test groups (1: Maxgraft®, freeze-dried, multiple donors, and 2: Puros®, solvent-dehydrated, single donor) and an autologous control group (10 patients). Plasma samples were collected pre-(T1) and postoperatively (2 weeks (T2) and 4 months (T3)). The Lymphocyte Transformation Test (LTT) was used for analyzing levels of transformed lymphocytes for type IV immune reactions by 3H-thymidine activity. Bone biopsies were harvested at T3 and immunohistochemically analyzed for IL-1α, IL1ß, TNF-α, CD4, CD8 and correlated with the immunological and clinical findings. Results A statistically significant difference between the tested materials was observed for LTT measurements at T3 (p = 0.033). Furthermore, three groups were identified: Group A (LTT negative T1-T3, n = 48), group B (LTT positive T1-T3, n = 7), group C (developing positive LTT at T2, n = 5). A highly significant elevation of IL-1α, IL1ß, TNF-α in patients of group C (p = 0.0001) and a significant elevation of CD4+ cells in patients of group B (p = 0.005) was shown. Conclusion Our data show that following allogeneic bone grafting, local and systemic immunological reactions can be detected in some patients. These findings were statistically significant for the timepoint T3 between the tested materials as well as for the groups B and C correlated with group A for both tested materials. Therefore, the null hypotheses were rejected. A preoperative compatibility test for allogeneic materials in order to improve patient safety and the predictability of these materials would be desirable. Trial registration Ethical commission of the Ärztekammer Hamburg, Germany (PV5211) as well as by the German Registry of Clinical Studies (DRKS00013010) on 30/07/2018 ( http://apps.who.int/trialsearch/ ).